Предмет:
АлгебраАвтор:
carsencuevas(m+2n-1)(m+2n+9)-(m-2n+1)(m-2n-9)≡(m+2n-1)(m+2n+1)-(m-2n+1)(m-2n-1) (mod 8)=((m+2n)²-1)-((m-2n)²-1)=(m+2n)²-(m-2n)²=m²+4mn+4n²-(m²-4mn+4n²)=8mn≡0(mod 8) ∀m,n∈Z
Это и означает, что ((m+2n-1)(m+2n+9)-(m-2n+1)(m-2n-9)) ⋮ 8
Ч.т.д.
_____________________
Использованы свойства сравнения чисел по модулю
Автор:
mombodp6zhДобавить свой ответ
Предмет:
ФизикаАвтор:
danteguerreroОтветов:
Смотреть
Предмет:
Английский языкАвтор:
jordansmtzОтветов:
Смотреть
Предмет:
МатематикаАвтор:
bambi32Ответов:
Смотреть
Предмет:
Русский языкАвтор:
matthewОтветов:
Смотреть